2016
DOI: 10.1051/0004-6361/201629309
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory spectroscopic study and astronomical detection of vibrationally excitedn-propyl cyanide

Abstract: Context. We performed a spectral line survey called Exploring Molecular Complexity with ALMA (EMoCA) toward Sagittarius B2(N) between 84.1 and 114.4 GHz with the Atacama Large Millimeter/submillimeter Array (ALMA) in its Cycles 0 and 1. We determined line intensities of n-propyl cyanide in the ground vibrational states of its gauche and anti conformers toward the hot molecular core Sagittarius B2(N2) which suggest that we should also be able to detect transitions pertaining to excited vibrational states. Aims.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 32 publications
(77 reference statements)
0
33
0
Order By: Relevance
“…The previous authors determined from intensity measurements that the anti conformer is lower in energy than the gauche by 1.1 ± 0.3 kJ mol −1 . Durig et al (2001) used infrared spectroscopy of n-PrCN dissolved in liquid Xenon to determine that the gauche conformer is lower than the anti by 0.48 ± 0.04 kJ mol −1 (or 58 ± 4 K) and Müller et al (2016) found this value to be fully consistent with their model of the ALMA spectra. Hirota (1962) also determined the rotational constants of the three lowest fundamental vibrational states of the anti and gauche conformers.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…The previous authors determined from intensity measurements that the anti conformer is lower in energy than the gauche by 1.1 ± 0.3 kJ mol −1 . Durig et al (2001) used infrared spectroscopy of n-PrCN dissolved in liquid Xenon to determine that the gauche conformer is lower than the anti by 0.48 ± 0.04 kJ mol −1 (or 58 ± 4 K) and Müller et al (2016) found this value to be fully consistent with their model of the ALMA spectra. Hirota (1962) also determined the rotational constants of the three lowest fundamental vibrational states of the anti and gauche conformers.…”
Section: Introductionmentioning
confidence: 86%
“…2. The experimental arrangement for measurements between 36−70 GHz and between 89.25−126.75 GHz have been described previously (Müller et al 2016). In the two new higher frequency ranges (171−251 and 310−506 GHz) we used a 5.1 m long double path (10.2 m total) absorption cell with inner diameter of 100 mm and equipped with Teflon windows.…”
Section: Laboratory Spectroscopic Detailsmentioning
confidence: 99%
See 3 more Smart Citations